COMPARATIVE STUDY OF EXPERIENCES OF WOMEN ACADEMIC LEADERS IN PUBLIC AND PRIVATE COLLEGES - Muzahir khan; Sultan Akbar Shah; Mr. Imran Khan; Aleeza Gul; Muhammad Mujtaba Haider; Iram Naeem (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2023)
In this study, female academic leaders in both public and private universities will be examined, and their experiences will be compared. The study will explore a range of leadership topics, such as difficulties faced, chances presented, chances for career progression, and work-life balance. The study aims to advance knowledge of the particular difficulties experienced by women in leadership roles in both public and private higher education institutions by exploring these issues.